Preparation and physicochemical characterization of sildenafil cocrystals - Somchai Sawatdee; Apichart Atipairin; Supitchaya Rakkummerd; Onsinee Suriyaphol; David J Harding; Poowadon Muenraya; Phimphaka Harding (Wolters Kluwer Medknow Publications, 2021)
Sildenafil is a specific inhibitor of the phosphodiesterase type 5 (PDE-5) enzyme that protects cyclic guanosine monophosphate from breakdown by PDE-5. It is a biopharmaceutical categorization system Class II medication with low bioavailability because it is almost insoluble in water. The objectives of this study were to prepare sildenafil cocrystals with co-former molecules including aspirin (acetylsalicylic acid [ASA]), fumaric acid (FMA), and benzoic acid (BZA) to improve the water solubility of sildenafil. The cocrystals were prepared by antisolvent addition (AA) and slow solvent evaporation (SE) methods. The stoichiometric ratios of sildenafil and co-former molecules were varied. The obtained crystals were characterized by stereomicroscope, Fourier transformed infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), and powder X-ray diffraction (PXRD). The water solubility of sildenafil cocrystals was compared with sildenafil base. In the AA method, the crystals only form in sildenafil-ASA reaction. These crystals were not cocrystals between sildenafil and ASA because they were formed to new substances that were confirmed by single-crystal X-ray diffraction. In the SE method, the cocrystals were successfully prepared in the reaction of sildenafil with ASA, FMA, and BZA which use acetone or ethyl acetate as a solvent. The obtained crystals are irregular shapes and their FT-IR, NMR, and PXRD results exhibited the characteristics of sildenafil and its co-former. The stoichiometric ratios of sildenafil and co-formers after cocrystallization were different from an initial of crystallization. The sildenafil cocrystals with ASA, FMA, and BZA by SE method had higher water solubility than sildenafil base. The sildenafil-FMA cocrystals had the highest water solubility and increased up to five times when compared with sildenafil base.